Investigation of Damages of Reinforced Concrete Precast Industrial Structures After 6 February 2023 Earthquakes - Atar, Muhammed; Ince, Ozan; Tas, Omer Faruk; Ozmen, Alper; Sayin, Erkut (Afet ve Acil Durum Yonetimi Baskanligi (AFAD), 2023)
On February 6, 2023, two devastating earthquakes occurred in Kahramanmaraş on the same day. In this study, the damages occurred in two reinforced concrete precast industrial structures after the Pazarcık (Mw 7.7) and Elbistan (Mw 7.6) earthquakes were investigated. There are different types of moment-transmitting and non-moment-transmitting connection types for precast structures in the Türkiye Building Earthquake Code (TBDY 2018), non-moment-transferring pinned connections are generally preferred in practice. Although pinned connections provide fast and practical application, they suffer brittle damages during earthquakes. In addition, there is a risk of out-of-plane collapse of the beams in these joints. In the field investigations, serious brittle damages were observed in the joints with pinned connections. When the earthquake damages are examined, it is seen that the joining methods that will provide ductile behaviour should be preferred in reinforced concrete precast structures. © 2023 AESSRA. All rights reserved.
Betonarme Prefabrik Endüstri Yapılarının 6 Şubat 2023 Depremleri Sonrası Hasarlarının İncelenmesi
Keywords: Earthquake; Precast structures; Seismic damage